The Future of the International Order in a Changing Strategic World - Younis Talat AlDabbagh; Mohammed Wael Al-Qissi (QALAAI ZANIST SCIENTIFIC JOURNAL, 2020)
The world has been systematized from decades into hierarchical arrangements which could be limited in accidence with the mechanisms moves of the states, their effective region, and the strategies of getting their goals. This arrangement is based on the powers that have much efficiency in the global system and the extent of the currency of the history movement. This epitomized for us the strategic principle “the states either rise up or decline, the aggregation of their rising or declining is as a result of a group of internal and external changes interlinking among them. They base deeply in the inputs, that is to say , measuring the inputs and outputs in a good manner, this realizes its systematized reality or not ,and it is through its way to obtain the desired strategic goals .This is where the overall global powers which the history had watched throughout its various periodical stays. The USA is the last power that has been dominating the world from the end of the cold war.